Prediction of Birth Weight of Newborn Nepalese’ Babies by Maximum Likelihood Estimation - Dhungana, Govinda Prasad (BMC Journal of Scientific Research, 2020)
The first weight of newborn babies is a vital indicator of their growth and progress in the performance of their life span. Normal birth weight children are healthier than low birth weight and overweight. Total 1111 data were taken from the 2016 NDHS data set and the R environment used to estimate the average birth of newborn babies. The maximum likelihood estimate of normal distribution is used to determine the average (SD) weight of newborn babies. The estimated value is validation by KS test and pdf plot with normal curve. Prevalence of low birth weight and overweight from the standard normal distribution has also been predicted. The mean weight of newborn infants of the children is (2.94 kg) 2940 grams and the standard deviation is (0.573 kg) 573 grams. The percentage of low birth weight and high birth weight is 22.04% and 3.14% respectively. The average weight of Nepalese newborn babies is ordinary, but the prevalence of low birth weight is still high in Nepal.